2018
DOI: 10.1556/004.2018.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary cereal type, crude protein and butyrate supplementation on metabolic parameters of broilers

Abstract: This study investigates the metabolic effects of maize- or wheat-based diets with normal (NP) and lowered (LP) dietary crude protein level [the latter supplemented with limiting amino acids and sodium (n-)butyrate at 1.5 g/kg diet] at different phases of broiler fattening. Blood samples of Ross 308 broilers were tested at the age of 1, 3 and 6 weeks. Total protein (TP) concentration increased in wheat-based and decreased in LP groups in week 3, while butyrate reduced albumin/TP ratio in week 1. Uric acid level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Dietary supplementation of protected butyrate provides butyrate release in more distal sections of the intestines, while unprotected butyrate is rapidly absorbed from the proximal section of the gastrointestinal tract (Kulcsár et al, 2017). These different kinetic properties of protected butyrate products should deliver better butyrate exposure for the intestinal microflora, and the prolonged absorption may also have differing effects on various extraintestinal tissues compared to the action of unprotected butyrate (Kulcsár et al, 2016(Kulcsár et al, , 2017Petrilla et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation of protected butyrate provides butyrate release in more distal sections of the intestines, while unprotected butyrate is rapidly absorbed from the proximal section of the gastrointestinal tract (Kulcsár et al, 2017). These different kinetic properties of protected butyrate products should deliver better butyrate exposure for the intestinal microflora, and the prolonged absorption may also have differing effects on various extraintestinal tissues compared to the action of unprotected butyrate (Kulcsár et al, 2016(Kulcsár et al, , 2017Petrilla et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this moderate responsiveness to insulin, the observed increase in IRβ and mTOR protein abundance in WB groups could be of outstanding importance in the activation of downstream elements of the signaling pathway, suggesting that there is an opportunity to find new ways of growth promotion in the broiler industry via the amelioration of insulin sensitivity. Notwithstanding that the present study was not designed to assess performance data, it should be noted as background information that the body weight of chickens was increased by applying WB and LP (limiting amino acid supplemented) diets, as published by Petrilla et al [ 46 ]. These results are in accordance with those of previous studies [ 28 , 30 ], and might be partly related to the detected amelioration of the IRβ and mTOR protein abundance in WB groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present study also showed promising results as the ADG and EBI were improved following optimal dietary TB administration at 1,840 mg/kg under the cost-saving formulating regime. Furthermore, several aggressive yet pioneered research showed that better weight gain and feed/gain ratio could be achieved when birds were fed diet with reduced crude protein and/or metabolic energy contents and supplemented with butyrate products ( M’Sadeq et al, 2016 ; Bortoluzzi et al, 2017 ; Petrilla et al, 2018 ; Mátis et al, 2019 ). Taken together, these results provided scientific proofs regarding the application of butyrate for cost-saving and better profit return formulas in poultry operation.…”
Section: Discussionmentioning
confidence: 99%